Innovative Control Technique for the Floor Heave in Goaf-Side Entry Retaining Based on Pressure Relief by Roof Cutting. (19th August 2021) - Yu, Guangyuan; Wang, Jiong; Hu, Jinzhu; Zhu, Daoyong; Sun, Han; Ma, Xingen; Ming, Wei; Li, Wenfei
Abstract : To solve the difficulty in controlling floor heave of a retained goaf-side roadway, a new control technique was investigated from the perspective of the pressure relief by roof cutting by combining mechanical analysis, numerical simulation, and engineering tests. The mechanical principle of controlling the floor heave based on pressure relief by roof cutting was attained by analyzing the movement of overlying strata and mechanical characteristics of key blocks before and after the roof cutting. A new technique for controlling the floor heave based on pressure relief by roof cutting was proposed. Research results have shown that after performing pressure relief by roof cutting, the caved gangues in the goaf can support the overlying strata and, thereby, change the movement law thereof and weaken the abutment pressure on the coal wall. Furthermore, the pressure exerted on the roadway floor by the coal wall is lowered to prevent plastic deformation of the floor, thus controlling floor heave in the roadway; a new integrated technique for controlling the floor heave based on pressure relief by roof cutting, flexible yielding, controlling with double-direction-control anchor bolts, and controlling with reinforcing anchor cables is developed, and the technological processes of support, cutting, and protection are summarised. The results of field testing showed that, after applying the new technique, the average floor heave amount of the roadway declines by 64% and the average speed of the floor heave up to 231 m behind the working face decreases by 61%.